Assessment of the strength of the lower limb muscles in subjects with stroke with portable dynamometry: a literature review - Júlia Caetano Martins; Larissa Tavares Aguiar; Eliza Maria Lara; Juliana Braga Moura; Lucas Araújo Castro e Souza; Luci Fuscaldi Teixeira-Salmela; Christina Danielli Coelho de Morais Faria
Abstract Introduction: Weakness of the lower limb muscles, which are the main impairments after stroke, is associated with reduced mobility and decreased performance in functional tasks. Therefore, the assessment of strength of these muscles is necessary, which is commonly assessed with portable dynamometry. Aims: To perform a literature review regarding the methods used to assess lower limb strength with portable dynamometry in subjects with stroke and to describe its investigated measurement properties with this population. Materials and Methods: An extensive search was performed on the MEDLINE, SCIELO, LILACS, and PEDro databases, by combining specific key words, followed by active manual search by two independent researchers. Results and Discussion: Thirty studies were included, and the muscular groups of the knee (90%) were the most assessed, followed by the ankle (66.7%) and hip (63.3%) joints. In 5% of the studies, there were not reported any descriptions related to the positioning of the subjects and the equipment, neither regarding the stabilization procedures. Only 50% provided information regarding the number of trials and only 46.7% regarding the contraction times, being three trials and 5s the most commonly applied. Only 10% provided feedback and 23.3% demonstrations, prior to data collection. Only seven studies (23.3%) investigated the measurement properties of portable dynamometry and reported moderate to high reliability levels. Final Considerations: The protocols used for the assessment of the strength of the lower limb muscles with portable dynamometry in subjects with stroke were not standardized. Moreover, only one measurement property was investigated: the reliability, which was considered adequate.